Determinants of Inter-Regional Financial Inclusion Heterogeneities in the Philippines - Burguillos, Je-Al; Cassimon, Danny (Asian Development Policy Review, 2021)
This study tries to contribute to the vast literature on promoting financial inclusion in Asia by exploring the key factors that affect the deepening of financial inclusion across the 17 regions of the Philippines for the period between 2013 and 2017. Using the regional multidimensional financial inclusion index (FII) that is developed by the Philippine central bank, the Bangko Sentral ng Pilipinas (BSP), the study finds out that significant heterogeneities exist among regions, and that they persist over the period analyzed, suggesting most importantly that the least financially inclusive regions do not show rapid significant progress. Moreover, using different panel estimation techniques, we try to determine the possible factors that affect this inter-regional financial inclusion heterogeneities. Overall, we show that regional GDP per capita, population, a proxy for the availability of physical infrastructure, and the degree of mobile penetration are among the robust factors explaining the financial inclusion variations across these regions in the Philippines for the observed period.